A SEMIOTIC ANALYSIS OF THE MESSAGE BEHIND THE INDIGENOUS FOODS IN THE TRADITIONAL TOBA BATAK MARRIAGE PROCESSION: THE INDIGENOUS MEAT OF PORK AND THE GOLD FISH - Regina Abigail Jade Calista; Handayani Hajar Aswati (Pimpinan Cabang Muhammadiyah Kramat Jati, 2020)
The research, aims to find out what meaning is contained in the customary food ritual of Pork and Gold Fish in the traditional Toba Batak marriage procession. This research uses qualitative research method of semiotics by using the main theory, that is Charles Sanders Pierce theory. Data collection is done by observation, direct interview with resource person, and literature study. From the results of this study it can be concluded that several meanings are contained in customary food of pork and goldfish according to the analysis of signs, objects, interpretations, and categories of signs in the form of icons, indices and symbols. The meanings that can be drawn from the traditional foods are a) The head (ulu) is made into 3 parts: 1) right upper jaw (na marngingi parsiamun), 2) upper left jaw (na marngingi parhambirang), 3) lower jaw (osang), b) tail (ihur-ihur), C) the circle of the neck (aliang-aliang), d) the circular backs to the ribs (eastern), e) the groin (soit), and goldfish (dekke mas) according to the division in Dalihan na tolu.